Analisis Koreksi Fiskal atas Pendapatan, Beban dan Pajak Tangguhan untuk Menentukan Besarnya Pajak Penghasilan yang Terutang pada PT. DCN Indonesia - Ramadhanti A., Fauzia Salsabila; Dewi, Santi Rahma (Innovative Technologica: Methodical Research Journal, 2023)
This study aims to analysis determines of fiscal corrections on income, expenses, and deferred taxes in PT. DCN Indonesia in determining the amount of income tax payable. In this study, the author uses qualitative research methods. Namely, author will prepare the data that has been obtained, interpreted, and then analyzed. From this study will be obtained information that can answer the problems faced., the use of data in secondary uses data such as commercial income statements and fiscal income statements as a list of assets and depreciation in the 2019 period. This research concludes that: (1) income and expenses in determining the income tax payable are not following the provisions of tax regulations due to different fiscal corrections between commercial reports and fiscal financial statements. (2) The amount of profit before tax is base on Financial Accounting Standards and profit before tax base on tax rules has a difference. (3) Several fiscal corrections were found in the income and expense accounts. (4) Calculation of deferred tax based on PSAK Number. 46 due to depreciation costs, resulting in time differences.